A dynamic systems approach to wait time in the second language classroom. (August 2017) - Smith, Lesley; King, Jim
Abstract: This study discusses how wait time—the silent pause after a teacher elicits a student response—alters classroom discourse. Previous wait time research suggests overall positive changes in both teacher and student discourse where wait time is over 1 s. However, such studies are primarily structuralist in nature and tend to reduce the intricacy of classroom behavior to distinct variables, which can be easily altered to achieve a desired result. The data presented here comes from a series of structured observations of a UK university postgraduate L2 classroom. The findings were as follows: 1) Wait time played an intricate role in determining classroom discourse patterns and heavily favored an IRF turn-taking sequence; 2) student-initiated discourse was low in all observations and favored higher proficiency students; 3) the length of individual student-initiated turns appears to have been more important than the overall number of student-initiated turns in determining the quality of classroom discourse and was not directly related to changes in wait time length; 4) extended wait time (over 2 s in length) temporarily shifted discourse out of an IRF pattern and into a new, more student-driven phase. While previously thought of as only a pedagogical tool to increase student speech, wait time is shown to be a phenomenon which develops and changes with the composite forces that affect other aspects of classroom discourse.